Deterioracion postcosecha y almacenamiento de raices de yuca - Wheatley, Christopher C.; Lozano, C.; Gómez, G. (International Center for Tropical Agriculture, 1983)
Different aspects related to deterioration, treatments to extend cassava root durability, and root storage practices are briefly reviewed. The initiation and subsequent level of deterioration of cassava roots is closely related to the presence of mechanical damage which is normally caused at harvest. A subjective methos that allows the percentage of deterioration to be assessed is described. The results obtained show that var. MCo1 22 is more susceptible than MCo1 113. Changes in the color of cassava are due to occlusion of the xylem vessel fascicles and to the production of fluorescent compounds in the parenchyma among which scopoletin was identified. The percentage of deterioration in roots of var. MCo1 22 varied from less than 20 percent up to 90 percent, indicating that this var. could be susceptible or resistant depending on the conditions at harvest and that it is difficult to determine the absolute degree of susceptibility of a var. Evaluations of postharvest deterioration in 5 localities in Colombia, under different edaphoclimatic conditions, showed that there is a wide range of deterioration among the var. at CIAT-Palmira and in Popayan, while in the northern coast of Colombia the level of deterioration was considerably lower. All of the var. were resistant in Carimagua. Var. MCo1 1807 and MCo1 22 were also found to be the var. most susceptible to deterioration before canopy pruning and the most resistant after pruning. (CIAT)